Comparisons of urinary bladder responses to common antimuscarinics reveals unique effects of darifenacin - Veer, Vineesha; Chess-Williams, Russ; Moro, Christian (Frontiers in Physiology, 2025)
IntroductionAntimuscarinics are the first-line pharmaceutical treatment for overactive bladder (OAB). However, some literature suggests that responses to these antimuscarinics can influence a variety of non-muscarinic receptors. This study aimed to identify any non-muscarinic influences on contraction from commonly prescribed clinical antimuscarinics using porcine detrusor or urothelium with lamina propria (U&LP) tissues.MethodsPorcine bladders were dissected into strips of juvenile or adult detrusor or U&LP. Carbachol concentration-response curves were performed on paired tissues in the absence or presence of commonly prescribed antimuscarinics: darifenacin, fesoterodine, oxybutynin, solifenacin, trospium, and tolterodine. Estimated affinities for each antimuscarinic were calculated, and maximum contraction values from control and intervention curves were compared. Experiments in the presence of darifenacin (100 nM) were completed with serotonin (100 µM), prostaglandin E2 (10 µM), histamine (100 µM), αβ-methylene-ATP (10 µM), angiotensin II (100 nM), neurokinin A (300 nM), and carbachol (10 µM).ResultsDarifenacin significantly reduced maximum contraction responses to carbachol in adult detrusor preparations by 46%, αβ-methylene-ATP by 50%, prostaglandin E2 by 73%, histamine by 64%, and serotonin by 53%. Darifenacin reduced the maximum contraction in adult U&LP preparations to carbachol by 49% and to αβ-methylene-ATP by 35%.DiscussionDarifenacin presents as an antimuscarinic medication that influences non-muscarinic pathways in urinary bladder tissue, indicating its potential to assist OAB patients with non-muscarinic pathophysiology.